Plasma-assisted mechanochemistry to produce polyamide/boron nitride nanocomposites with high thermal conductivities and mechanical properties. (1st May 2019) - You, Jiwan; Choi, Han-Hyeong; Lee, Young Mo; Cho, Jaehyun; Park, Min; Lee, Sang-Soo; Park, Jong Hyuk
Abstract: Polymer nanocomposites incorporating nanofillers have achieved a variety of functionalities including mechanical, chemical, thermal, and electrical properties. However, the fundamental problem in such composites, poor compatibility between polymers and nanofillers, has limited the development of functionalities. Herein, we demonstrate a simple and effective approach to address this issue without using compatibilizers. The plasma-assisted mechanochemistry (PMC) process can readily form covalent bonds between polymers and nanofillers even in the solid state, providing excellent processability; it is also cost effective and environmentally friendly. Polyamide 66 (PA66) and hexagonal boron nitride (h-BN) were compounded via the PMC process, which enhanced the interfacial affinity between PA66 and h-BN and promoted uniform dispersion of h-BN platelets in the composites. The resulting PA66/h-BN nanocomposites exhibited significantly improved mechanical properties and thermal conductivities. In particular, the degradation in tensile strength of the composites at high h-BN content was completely prevented by the PMC process and the thermal conductivities of the composites were over four times higher than those of conventional composites. Therefore, this approach can produce polymer nanocomposites with improved functionalities, thus greatly extending their applications.